Integrating Survey Data and Digital Trace Data: Key Issues in Developing an Emerging Field. (October 2020) - Stier, Sebastian; Breuer, Johannes; Siegers, Pascal; Thorson, Kjerstin
While survey research has been at the heart of social science for decades and social scientific research with digital trace data has been growing rapidly in the last few years, until now, there are relatively few studies that combine these two data types. This may be surprising given the potential of linking surveys and digital trace data, but at the same time, it is important to note that the collection and analysis of such linked data are challenging in several regards. The three key issues are: (1) data linking including informed consent for individual-level studies, (2) methodological and ethical issues impeding the scientific (re)analysis of linked survey and digital trace data sets, and (3) developing conceptual and theoretical frameworks tailored toward the multidimensionality of such data. This special issue addresses these challenges by presenting cutting-edge methodological work on how to best collect and analyze linked data as well as studies that have successfully combined survey data and digital trace data to find innovative answers to relevant social scientific questions.